The Case of Paul's Death: The Role of Memory in the Quest for the "Historical Paul" - Bulundwe, Luc (Early christianity, 2024)
The undisputed letters have long seemed the best source in the quest for the "historical Paul." Aheated debate drew a hard line between what has been referred to as the "real Paul" - the author of the seven undisputed letters - and the so-called "Paul of tradition" - the one described in the first reception. This debate, however, has somewhat subsided. In this article, I argue that this de-escalation can be attributed in large part to the insight of social memory approaches. Indeed, through a memory perspective, texts not written by Paul have been reconsidered in the search for who Paul was. Paul's death, a test case, shows that 2 Timothy and the Acts of the Apostles fill out a "breakdown in tradition" in Paul's cultural memory by highlighting features such as Paul'sheroic journey to his death and its location in Rome. The two texts, while respecting the framework set by the undisputed letters, also confirm two historical details of Paul's death. The fate of Paul's cultural memory changed, however, when some of his receptions emphasized some features and omitted others. In some of the receptions, the change is significant enough that the role Paul attributes to the death of Christ is transferred to the death of Paul.